Photovoltaic performance of hybrid ITO/PEDOT:PSS/n-SnS/Al solar cell structure. (July 2016) - Jain, Priyal; Arun, P.
Abstract: The present paper discusses the performance of ITO/PEDOT:PSS/n-SnS/Al structured solar cells fabricated by thermal evaporation. The performance characterizing parameters such as the open circuit voltage, short circuit current density, series resistance, parallel resistance, ideality factor and the overall efficiency were found to be dependent on the SnS grain size in the nano-meter regime and incident light intensity. The experimental work directly reconfirms the theoretical results and ideas raised in the literature by early researchers.